Calidad vinculada al origen: Marcas Colectivas, herramientas de valorización y comercialización para productos agrícolas y artesanales de Cotopaxi, mecanismos alternativos de Desarrollo Local. - Llumiquinga Jiménez, Lorena Paola (2020)
The present investigation is developed around the protection of the products of origin by means of Intellectual Property mechanisms such as Collective Marks, tools which allow to value and commercialize the endogenous resources of the different localities of the Cotopaxi province. This investigation frames in the analysis, conservation and exploitation of biodiversity, associated with topics of culture, heritage and ancestral knowledge. The objective is the development of a methodological proposal which constitutes a guide for small and medium producers who are immersed in the value chain of products of origin. The intention is to raise awareness about the potential relationships that exist between territories-products-people, trying to generate an economically profitable, socially just and ecologically sustainable system. This research is descriptive and the method used was qualitative one, allowing to guarantee our own experiences. As an initial result it determined that two associations, of the eight mentioned, presented characteristics to initiate a traceability process through a collective mark, based on these criteria, we worked xi on the components of the methodology being: identification and qualification of the product, remuneration, reproduction of local resources and public policies.